SISTEM INFORMASI COMPANY PROFILE PADA CV. ALEXA CIPTA TEKINDO MENGGUNAKAN METODE FORWARD CHAINING SEBAGAI MEDIA PROMOSI SERTA INFORMASI - Andhika Dwi Irawan, Falah; Zein Vitadiar, Tanhella (Inovate, 2023)
Forward chaining is a method of finding starting with known facts and matching those facts with IFand IFTHEN. If any facts match IF, the rule is executed. If a rule is executed, the new facts are included in thedatabase. Every shuffle starts at the top of the rule. Each rule can only be executed once and the process stops ifno rule can be executed. Therefore, the Forward Chaining method is very suitable for solving problems inchoosing a decision, such as choosing an internet package that suits your needs. Internet package is a quota orinternet network speed that has been grouped into several packages. Here Alexa.net which is a companyengaged in internet network provider services for homes or other public places that sell several internetpackages really need this method to help buyers choose the appropriate internet package. The process ofpromotion and sale of the internet package will use the website. Website is an internet facility that deals withdocuments within near or far areas. Documents on the website or web page and website links allow users toswitch from one page to another. Company Profile is a universal description of a company that will carry out aseries of integrated promotions through writing that will also be placed on the website.Keywords: Forward Chaining, Internet Package, Alexa.net, Website, Company Profile.